Selection of various synthetic Maize (Zea mays L.) genotypes on drought stress condition. (February 2019) - Farid, M; Musa, Y; Nasaruddin,; Ridwan, I
Abstract: A study was conducted with the aim of selecting synthetic maize genotypes tolerant to drought. The study was conducted at Experimental Farm, Faculty of Agriculture, Hasanuddin University from July to November 2017. The experiment was carried out in the form of Split Plot Design with irrigation as main plot and genotypes as subplot. Two irrigation conditions were applied to create normal and drought condition. Six synthetic maize genotypes and three comparative varieties (Bisma, Lamuru, and Sukmaraga) were used. The results showed that the genotypes Syn 2-15, and Syn 2-16 were the synthetic maize genotypes which produced higher yield and were classified as medium tolerant (MT) to drought with productivity of 6 t.ha −1 and 6.48 t.ha −1, respectively. These yields were significantly different from the varieties of Bisma and Sukmaraga in drought stress conditions. Therefore it can be concluded that adaptive synthetic maize genotypes that are provided a potential yield of ≥ 6.0 t.ha −1 in environmental stresses were Syn2-15, and Syn2-16.